The Impact of the Indonesian Financial Crisis on Children : Data from 100 Villages Survey - Cameron, Lisa A. (World Bank, Washington, D.C., 2013)
The author examines the Asian crisis's impact on children in 100 Indonesian villages, based on data from four rounds of the 100 villages surveys that was used to examine changes in health status, school attendance rates, and children's participation in the labor force. She finds little evidence that the crisis had a dramatically negative impact on children. School attendance dropped slightly after the onset of the crisis but then rebounded to higher-than-pre-crisis levels. Fewer children are now working, although the older children who are working and are not attending school seem to be working longer hours. Children's health status appears to be relatively stable, although comparisons of indicators of children's health status over time are complicated by changes in the questionnaire used. The author also examines ways households reported they were coping with the crisis.